Morphology, microstructure and mechanical properties of synthesized nano-sized alumina - Dela Cuesta, Lina C. (2005)
Alumina powders were synthesized from aqueous solutions of ammonium aluminum sulfate (AA) and ammonium hydrogen carbonate (AHC) at pH 6.5 and pH 8.5. In acidic medium (pH 6.5), the alumina immediately precipitated, whereas in basic medium (pH 8.5), the alumina precipitate remained dispersed and took time to settle. Based on the XRD analysis, the powder prepared at pH 6.5 was Al (OH)3 and had an amorphous structure. On the other hand, the powder made at pH 8.5 was ammonium aluminum carbonate hydroxide (AACH) and gave a crystalline structure. Both powders exhibited fine particle size, although the amorphous one was coarser.
When these powders were heated at 1300 degree celcius, various physical and chemical changes occurred. The DTA results showed that the powders prepared at pH 6.5 Al (OH)3, possessed three endothermic peaks and three exothermic peaks. The endothermic peaks corresponded to the evolution of adsorbed water, the removal of the water of crystallization and the final stage of the evolution of water of crystallization. The exothermic peaks suggested the presence of Al2O3 intermediates in the form of y-Al2O3 and 0-Al2O3 prior to the formation of the thermodynamically stable x-Al2O3 at 1190 degree celcius.
The crystalline type alumina powder (AACH) showed also three endotherms and two exotherms. The first endotherm resulted from the removal of adsorbed water. The second endotherm was the evolution of combustible in the forms of ammonia, carbon dioxide and water resulting from the degradation of AACH upon heating. The last endothermic peak corresponded to the excess water of crystallization. The powder made at pH 8.5 gave only one unstable y-Al2O3 before the formation of the x-Al2O3 at 1220 degree celcius. The alumina intermediates were characterized using x-ray diffraction after the calcinations of these powders at specific temperatures as recorded by the DTA.
The alumina powders were compacted by cold isostatic pressing (CIP) and hot isostatic pressing (HIP) and sintered at 1550 degree celcius and 1650 degree celcius. The densities of the CIP and HIP sintered compacts have not attained the desired theoretical density due to the presence of pores. This was significant for the compacts prepared at pH 8.5. The low density was attributed to the fine and agglomerated structure of the powders that reduced good compaction.
The developed microstructures of the CIP and HIP alumina compacts were very much dependent on two factors: (1) presence of an impurity and (2) sintering temperature and atmosphere being adapted. These factors contributed to the occurrence of grain growth in all sample compacts. Data showed that the CIP alumina compacts gave irregular shapes of grains due to the abnormal growth of the grains which was appreciably large in pH 8.5 when sintered at 1650 degree celcius under oxidation atmosphere. In the case of the HIP alumina compacts, grain growth was not noticeably observed in the SEM micrographs of the acidic and basic alumina. But the existence of such grain growth was clearly observed from the laser micrographs. The contamination of the alumina with Ca (calcium), was validated by the results taken from EDAX analysis.
The flexural strength and fracture toughness were very much dependent on the developed microstructure of the alumina compacts. The HIP fabricated compacts exhibited better mechanical properties due to their finer microstructure with the presence of needle like structures in between the grains. This was effective in deflecting the propagation of cracks, thus, the fracture toughness increased correspondingly. The needle like structure was attributed to the Ca impurity which was homogeneously mixed with the sample prepared at pH 8.5.
Thesis (Ph.D. Materials Science and Engineering)--University of the Philippines, 2005.